Codzienność rozszczelniona. O "Codziennej walce" Manu Larceneta - Kaja, Damian (Załącznik Kulturoznawczy, 2023)
In the proposed reading of Manu Larcenet’s Le Combat Ordinaire, everyday life appears not only as the setting of the story but also its fundamental—though by no means obvious, despite the abundance of everyday life imagery and motifs—theme. In Larcenet’s unspectacular narration, conducted in a tone oscillating between buffo and serious, human day-to-day affairs, obscured by the facade of ritual, appear as an effort, a task to complete, a risk to be taken, a problem of existence in the “cracks” of which the most important experiences occur, defined by the dialectics of life and death, health and illness, nature and culture, order and disorder. The article presents an analysis of the key dimensions of this “everyday struggle:” from the textual game whose stake is the axiology of everyday life (the issue of intimate diary, the value of journalism as a profession), to the sense of locality and the construction of identity based on memory and postmemory, to use Marianne Hirsch’s concept (references to the war in Algeria). The interpretation of Larcenet’s graphic novel was carried out based on three premises: (1) the everyday settles into fiction thanks to mimesis; (2) contact with everyday life may lead to an epiphanic revelation of a spiritual truth (drawing on Jolanta Brach-Czaina’s concept described in her philosophical essay Szczeliny istnienia [Cracks in Existence], this phenomenon can be called the “unsealing” of everyday life); (3) literary depictions of human daily existence are where literature and sociology intersect, as a result of which literary works (or, comics in this case) help reveal the structures of everyday life.